Climate Change and the Muslim World: The OIC Can do with ‘Captain Planet’ - Jamil, Sofiah (2016)
WHILE the media incessantly highlights the Muslim world’s battle with Islamophobia and the political crises in Iraq, Gaza and Iran, another set of issues that is just as pertinent -but often overlooked is climate change. According to the World Meteorological Organisation, 90% of the global disasters that occurred between 1993 and 2002 were weather, climate or water-related. Recent reports by Sir Nicholas Stern and the United Nations Framework Convention on Climate Change (UNFCCC) highlighted the immense adversities that climate change has, and could have, on the environment and economic development.